Evaluation of the Effects of Retro-Cavity Preconditioning with or Without Ethylenediaminetetraacetic Acid on Root Surface pH and Dislodgement Resistance of NeoMTA2 and Mineral Trioxide Aggregate Flow Retro-Fills: An Ex Vivo Investigation - Sedigheh Khedmat; Seyyed Ali Abaee; Hadi Assadian; Antonio Signore; Stefano Benedicenti (Journal of Functional Biomaterials)
Background: The aim of this study was to investigate the effects of retro-cavity preconditioning with or without 17% ethylenediaminetetraacetic acid (EDTA) solution on root surface pH as well as dislodgement resistance of NeoMTA2 and MTA Flow retro-fills. Methods: Forty-eight single-rooted human incisors were selected. After completion of endodontic treatment, root-end resections were performed, and retro-cavities were prepared. The samples were randomly divided into two groups of A and B (n = 24 each). In group A, retro-cavities were preconditioned with 2.5% NaOCl, followed by 17% EDTA solution, whereas in group B, preconditioning was performed using 2.5% NaOCl before final irrigation with normal saline. Samples in each group were randomly subdivided into two subgroups of 1 and 2. Retro-fillings in the A1 and B1 subgroups were performed with MTA Flow, and in the A2 and B2 subgroups, they were performed with NeoMTA2. Root surface pH was measured in each sample at three different stages: before preparation of retro-cavities (pH0), after retro-cavity preconditioning (pH1), and three days after retro-filling (pH2). Subsequently, the push-out bond strength (PBS) of the retro-filling materials was measured by a universal testing machine, and their failure modes were visualized under 64× magnification. Results: Preconditioning with EDTA caused a significant increase in PBS for both NeoMTA2 and MTA Flow (p < 0.001). There was no significant difference between the average bond strength of MTA Flow and Neo MTA2 (p = 0.271). There was a significant increase in the average pH2 compared to pH1 and pH0 across all groups (p < 0.001). Specifically, the use of EDTA led to a notable increase in the average pH2 in the MTA Flow group compared to the Neo MTA2 group (p = 0.027). Groups preconditioned with EDTA more frequently indicated a cohesive failure mode. Conclusions: The use of EDTA significantly increased the push-out bond strength of retro-fill materials to dentin. However, it did not prevent the ultimate alkalinity of retro-filled cavities.